A guide to the legal framework of the PSM standard for engineers. Issue 2 (30th October 2013) - Cunio, Christopher; Melhem, Georges
<x xml:space="preserve">Abstract</x> Compliance with the Process Safety Management (PSM) Standard is challenging for even the most sophisticated operators because of the broad scope and highly technical nature of the 14 PSM elements. This article provides guidance on how to comply with the three elements most frequently cited by OSHA—process safety information, process hazards analysis, and mechanical integrity—and the consequences of a failure to do so. © 2013 American Institute of Chemical Engineers Process Saf Prog 33: 152–155, 2014